Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/3219490
|View full text |Cite|
|
Sign up to set email alerts
|

Ketamine Administration Reverses Corticosterone-Induced Alterations in Excitatory and Inhibitory Transmission in the Rat Dorsal Raphe Nucleus

Abstract: Ketamine, a N-methyl-D-aspartate (NMDA) receptor antagonist, exerts rapid antidepressant effects in human patients and ameliorates depressive-like behavioral effects of chronic stress in animal models. Chronic stress and elevated corticosterone levels have been shown to modify serotonin (5-HT) neurotransmission, and ketamine’s antidepressant-like activity involves a 5-HT-dependent mechanism. However, it is not known if and how ketamine affects the electrophysiological characteristics of neurons and synaptic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…We have previously observed a superficially similar reduction in the frequency of sIPSCs which occurred in rat DRN projection neurons after repeated corticosterone administration (Sowa, Kusek, Bobula, Hess, & Tokarski, 2019; Sowa et al., 2018). Moreover, we have found that long‐lasting elevation in plasma corticosterone levels increases sEPSC frequency in DRN projection cells (Sowa et al., 2019), which resembles our current observations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We have previously observed a superficially similar reduction in the frequency of sIPSCs which occurred in rat DRN projection neurons after repeated corticosterone administration (Sowa, Kusek, Bobula, Hess, & Tokarski, 2019; Sowa et al., 2018). Moreover, we have found that long‐lasting elevation in plasma corticosterone levels increases sEPSC frequency in DRN projection cells (Sowa et al., 2019), which resembles our current observations.…”
Section: Discussionsupporting
confidence: 54%
“…We have previously observed a superficially similar reduction in the frequency of sIPSCs which occurred in rat DRN projection neurons after repeated corticosterone administration (Sowa, Kusek, Bobula, Hess, & Tokarski, 2019; Sowa et al., 2018). Moreover, we have found that long‐lasting elevation in plasma corticosterone levels increases sEPSC frequency in DRN projection cells (Sowa et al., 2019), which resembles our current observations. Prenatal stress imposed by a procedure identical to the one used in the present study and performed on the same rat strain (Sprague‐Dawley) has earlier been shown to induce a hyperactivity of the hypothalamic–pituitary–adrenal (HPA) axis in response to acute stressors and to elevate basal plasma corticosterone levels at least during part of the day (Szymańska et al., 2009).…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, ketamine failed to reverse swim stress-induced decrease of digging; however, this could be due to a compounding effect as a single injection of ketamine has been shown to increase corticosterone in rats following chronic corticosterone administration (Wegman-Points et al, 2020). However, there are plenty of studies demonstrating ketamine’s ability to reverse corticosterone-induced depression of behavior and cellular signaling (Fraga et al, 2021; Sowa et al, 2019; Wang et al, 2019). The lack of ketamine effect in following swim stress could be due to several variables including, but not limited to, dose tested, pretreatment time on test days, and/or dosing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In the article titled “Ketamine administration reverses corticosterone-induced alterations in excitatory and inhibitory transmission in the rat dorsal raphe nucleus” [ 1 ], there was an error in Figures 2 and 3 . Figures 2 and 3 images were swapped.…”
mentioning
confidence: 99%